Nano strain induced double columnar oxide as highly active oxygen-dissociation electrode for Ni-Fe metal supported solid oxide fuel cells. (February 2019) - Kang, Byeong Su; Matsuda, Junko; Ju, Young Wan; Kim, Hack Ho; Ishihara, Tatsumi
Abstract: A double columnar structure film consisting of Sm0.5 Sr0.5 CoO3-δ (SSC) and Sm0.2 Ce0.8 O3-δ (SDC) as an active cathode was prepared by pulsed laser deposition (PLD) on a thin La0.9 Sr0.1 Ga0.8 Mg0.2 O3-δ /SDC bi-layer film, and the effects of SSC/SDC ratio in double columnar layer on cathodic performance were investigated. It was found that the cathodic overpotential as well as power density were strongly dependent on SSC-SDC ratio in double columnar layer. Almost the theoretical open circuit potential (1.10 V) and extremely high maximum power density higher than 3.0 and 0.33 W/cm 2 at 973 and 773 K respectively, were achieved on the cell using double columnar at SSC:SDC= 6:4 cathode, which is the optimized composition. Increased cathodic performance of double columnar SSC-SDC cathode were assigned to the decreased activation and the concentration overpotential. From XRD and TEM analysis, tensile strain in SDC and compressed one in SSC were observed, which could be increased diffusivity of oxide ion in SDC part. On the other hand, Sr surface segregation in SSC was prevented by the double columnar structure from low energy ion scattering (LEIS) spectroscopy and this could be related to the compressed strain in SSC part of double columnar structure resulting in the increased surface activity to oxygen dissociation. Graphical abstract: Highlights: The effect of the double columnar layer composition on the cathodic activity was further studied. The Nano size SSC-SDC double columnar layer improves cathodic activity for ORR. Strain engineering occurs in double columnar layer. Sr segregation is prevented by introducing SSC-SDC double columnar layer.